Wages, sex-discrimination and the Irish labor-market for young workers - Reilly, Barry (Economic & Social Studies, 1987)
Human capital wage equations are estimated using individual level data on single males and single females in the Irish labour market for young workers. The results are broadly consonant with theoretical predictions. Returns to on-the-job training and educational qualifications are reported and, in the latter case, are on average higher for the single males. Estimates of sex discrimination based on the unexplained differential from a reduced form equation are also reported. The findings suggest that the observed differential in wages that exists between young males and young females in the sample is, in large part, explained by differing characteristics. A small unexplained residual, interpreted under certain assumptions as an estimate of sex discrimination, is detected. However, the discrimination element is not found to be statistically significant.
Keywords: Sex discrimination - Ireland; Women's pay - Ireland